Determination of essential and toxic elements including natural radionuclides in some vegetables grown in Cameron Highlands, Pahang / Prof. Madya Dr Hj Zaini Hamzah and Marlinda Musa - Musa, Marlinda (Research Management Institute (RMI), 2012)
There are many essential and non-essential elements including metals and radionuclides present in vegetables. However, the accumulation of the several metals and radionuclides may cause contamination to vegetables which later on passed on to the consumer. Green mustard (Brasissca rapa var. Parachinesis L) and watercress (Nasturtiumm microphyllum/ officinale) were selected to represent the vegetable in this study. Objectives of this study are to determine the concentration of metals and radionuclides in the samples and to calculate the enrichment factor (EF) and also to estimate the uptake, base on biological accumulation coefficient (BAC), for the various parts of selected vegetables. This study also explore the extent of Naturally Occuring Radioactive Materials (NORM) distribution by calculating radium equivalent, absorbed dose, annual effective dose, external hazard index and index of geoaccumulation (/geo). Three vegetable farms in Cameron Highlands were studied namely Bharat, Kg Raja and Bertam. All samples (vegetables, soils and fertilizers) except for water samples were dried and converted into powder for measurement. Water samples were acidified using HNO36 M until pH2 before analysis. Samples analyses were done by using X-rays Fluorescence Spectroscopy (XRF) to measure the concentrations of Fe, Zn, Hg, U and Th; while for radioactivity concentrations, the measurement were done by using high resolution hyperpure germenium (HPGe) detector gamma spectrometry. The concentration of all elements in the soils is lower than their concentration in the control soil, except for Zn, U and Th. The concentration of all elements in Green Mustard is lower than their concentration in the soil where it was grown. The EF values in the Brasissca rapa var Parachinesis L are lower than 2 except for U and Th, indicating some degree of contamination due to anthropogenic activities or naturally origin. The BAC values show that Zn and Hg were accumulated in the green mustard and watercress. The radiation hazard for samples were greater than unity and there is no contamination of naturally occuring radioactive material (/geo < 1). Generally, only 40K uptake was observed in watercress and no indication that the plant and the study area are of radiological risk.